Experiment with plants - Byles, Monica (Minneapolis : Lerner Publications, 1994)
Presents basic information on plants and simple experiments that demonstrate some of their characteristics.
Includes index.
Booklist.
Horn Book.
School Library Journal.
4.9.
4.9
Keywords: Botany -- Experiments -- Juvenile literature; Gardening -- Experiments -- Juvenile literature; Experiments; Plants -- Experiments; Plants -- Experiments